2017
DOI: 10.7567/jjap.57.01af04
|View full text |Cite
|
Sign up to set email alerts
|

Formation of L12modified Al2.5Cu0.5Ti phase by heat treatment of spark-plasma-sintered Cu/Al3Ti specimens

Abstract: In our previous studies, the influence of L1 2 modified Al 2.5 Cu 0.5 Ti and Al 2.7 Fe 0.3 Ti particles on the grain refining performance of an Al cast was studied. It has been shown that the L1 2 modified intermetallic compound particles act as heterogeneous nucleation sites of α-Al solidification. Since nuclei are formed on the surface of the heterogeneous nucleation site particles, only the surface region of the Al 3 Ti particles must be modified into an L1 2 structure. In this study, therefore, the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It is known that grain boundaries and dislocation provide extra diffusion channels. [ 22 ] If grain boundary diffusion is significant, then that can explain the faster decomposition of the gas‐atomized Al 2.5 Cu 0.5 Ti particles as compared with crushed Al 2.5 Cu 0.5 Ti particles in the Al matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that grain boundaries and dislocation provide extra diffusion channels. [ 22 ] If grain boundary diffusion is significant, then that can explain the faster decomposition of the gas‐atomized Al 2.5 Cu 0.5 Ti particles as compared with crushed Al 2.5 Cu 0.5 Ti particles in the Al matrix.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that grain boundaries and dislocation provide extra diffusion channels. [22] If grain boundary diffusion is significant, then that can explain the faster decomposition of the gas-atomized Al 2.5 Cu 0.5 Ti particles as compared with crushed Al 2.5 Cu 0.5 Ti particles in the Al matrix. The microstructures of Al-10 vol%(Al 2.5 Cu 0.5 Ti) specimen fabricated by SPS and heat treated at 750 °C for 3, 5, and 10 min are shown in Figure 6a-c, respectively.…”
Section: Microstructure Of Al-10 Vol%(al25cu05ti)-layered Specimenmentioning
confidence: 99%
“…An L1 2 modified Al 2.5 Cu 0.5 Ti intermetallic compound can be formed at the Cu/Al 3 Ti interface in the Cu/Al 3 Ti diffusion couple specimen heated at elevated temperature as shown in Fig. 2 [12]. Therefore, it is expected that these intermetallic compounds show good grain refining performance.…”
Section: Introductionmentioning
confidence: 98%
“…Micrographs showing the interface in the Cu/Al 3 Ti diffusion couple specimen heated at 600 o C for 4 h[12].…”
mentioning
confidence: 99%
“…In our previous studies, [14][15][16][17] it has been shown that L1 2 modified (Al 1−x Me x ) 3 Ti intermetallic compounds [18][19][20][21] show good grain refining performance, although L1 2 modified (Al 1−x Me x ) 3 Ti intermetallic compounds cannot coexist with the Al matrix in an equilibrium state. Al-10 vol%Al 2.7 Fe 0.3 Ti and Al-10 vol%Al 2.7 Ni 0.3 Ti refiners with M values of 2.50 × 10 −3 and 1.93 × 10 −3 , respectively, are successfully fabricated by spark plasma sintering (SPS).…”
Section: Introductionmentioning
confidence: 99%